2014
DOI: 10.1044/2013_lshss-13-0009
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Skills in English Language Learners

Abstract: The results were consistent with the hypotheses outlined in Flege's (1995) speech learning model in that the phonological skills of ELLs increased over time and as a function of age of arrival and time. Thus, speech-language pathologists (SLPs) also should expect phonological skills in ELLs to increase over time, as is the case in monolingual children. SLPs can use the longitudinal and connected-speech results of this study to interpret their assessments of the phonological skills of ELLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
0
17
0
3
Order By: Relevance
“…They are observed in the speech of very young children whose phonological systems do not yet match the complexity of an adult's (Edwards & Shriberg, 1983;Grunwell, 1985;Stoel-Gammon & Dunn, 1985). A number of studies have investigated the occurrence of phonological processes in the speech of children who are typically developing bilingual or ELL (Anderson, 2004;Goldstein, Fabiano, & Washington, 2005;Holm & Dodd, 1999;Morrow, Goldstein, Gilhool, & Paradis, 2014).…”
Section: Japanese Phonotactic Constraints and Resulting English Phonomentioning
confidence: 99%
“…They are observed in the speech of very young children whose phonological systems do not yet match the complexity of an adult's (Edwards & Shriberg, 1983;Grunwell, 1985;Stoel-Gammon & Dunn, 1985). A number of studies have investigated the occurrence of phonological processes in the speech of children who are typically developing bilingual or ELL (Anderson, 2004;Goldstein, Fabiano, & Washington, 2005;Holm & Dodd, 1999;Morrow, Goldstein, Gilhool, & Paradis, 2014).…”
Section: Japanese Phonotactic Constraints and Resulting English Phonomentioning
confidence: 99%
“…A relevant finding to understanding this interaction is the rate at which ELLs acquire the L2 phonology. Previous research has found rapid mastery of English phonemes by ELLs (e.g., Anderson, 2004;Morrow et al, 2014). For example, using proportion of whole word proximity, a measure of whole-word accuracy, Morrow et al (2014) reported that by 21 months of exposure, ELL children with diverse L1 backgrounds were producing 93.4% of words in an English spontaneous speech sample correctly.…”
Section: Discussionmentioning
confidence: 99%
“…These questions are meant to more specifically examine the extent to which the structure of the nonwords (i.e., phonotactics) and children's L1 background impact performance. Based on L2 phonological developmental trends (Morrow et al, 2014), ELLs were predicted to have greater difficulty with coda consonants, regardless of their L1. Furthermore, the Chinese group was predicted to have depressed accuracy with coda consonants when compared to the South Asian group because of the crosslinguistic differences in word syllable structure described above.…”
Section: The Present Studymentioning
confidence: 99%
“…Morrow and colleagues found that age of acquisition to English and length of exposure to English were important predictors in the phonological abilities of English language learners from a variety of language backgrounds. 30 Children in their study who achieved the highest levels of English accuracy started learning English earlier and had more years of experience with English than other children in the study.…”
mentioning
confidence: 91%
“…29 Finally, a few studies provide evidence of bidirectional influence of the two languages for bilingual children. 19,30 Several methodological issues of existing studies affect the ability to determine whether bilingual children perform differently from their monolingual peers on phonology measures. Most studies did not systematically consider factors such as age of exposure to each language, relative amount of exposure to each language, use patterns for each language, or proficiency in each language.…”
mentioning
confidence: 99%